Uncoupling Foam Fractionation and Foam Adsorption for Enhanced Biosurfactant Synthesis and Recovery - Christian C. Blesken; Tessa Strümpfler; Till Tiso; Lars M. Blank (Microorganisms, 2020)
The production of biosurfactants is often hampered by excessive foaming in the bioreactor, impacting system scale-up and downstream processing. Foam fractionation was proposed to tackle this challenge by combining in situ product removal with a pre-purification step. In previous studies, foam fractionation was coupled to bioreactor operation, hence it was operated at suboptimal parameters. Here, we use an external fractionation column to decouple biosurfactant production from foam fractionation, enabling continuous surfactant separation, which is especially suited for system scale-up. As a subsequent product recovery step, continuous foam adsorption was integrated into the process. The configuration is evaluated for rhamnolipid (RL) or 3-(3-hydroxyalkanoyloxy)alkanoic acid (HAA, i.e., RL precursor) production by recombinant non-pathogenic Pseudomonas putida KT2440. Surfactant concentrations of 7.5 gRL/L and 2.0 gHAA/L were obtained in the fractionated foam. 4.7 g RLs and 2.8 g HAAs could be separated in the 2-stage recovery process within 36 h from a 2 L culture volume. With a culture volume scale-up to 9 L, 16 g RLs were adsorbed, and the space-time yield (STY) increased by 31% to <semantics>0.21 gRL/L·h</semantics>. We demonstrate a well-performing process design for biosurfactant production and recovery as a contribution to a vital bioeconomy.